Impact of Intrinsic Motivation on Organizational Commitment: An Islamic Banking Perspective (Journal of Asian Development Studies, 2013)
The research study discuss about the impact of intrinsic motivation on organizational commitment among Islamic Bank employee. Islamic banking is a new phenomenon in the Asian countries as Pakistan; particularly in this decade, with the aim to implement Shariah based Human resource practices and their implementation. In this study, the relationship between intrinsic motivation and organizational commitment was studied. Questionnaire survey was used as a primary data tool to gather information from the unit of analysis, which were individual employee of the Islamic Banks. The results of the research study show that there exists the relationship between intrinsic motivation and organizational commitment. The reasons for this significance were the difference in behaviors, attitudes, and perceptions of the employees.